Review on heat transfer analysis in thermal energy storage using latent heat storage systems and phase change materials - Sarbu, Ioan; Dorca, Alexandru (International journal of energy research, 2019)
Summary Thermal energy storage (TES) is a technology that stocks thermal energy by heating or cooling a storage medium so that the stored energy can be used later for heating and cooling applications and for power generation. TES has recently attracted increasing interest to thermal applications such as space and water heating, waste heat utilisation, cooling, and air conditioning. Phase change materials (PCMs) used for the storage of thermal energy as latent heat are special types of advanced materials that substantially contribute to the efficient use and conservation of waste heat and solar energy. This paper provides a comprehensive review on the development of latent heat storage (LHS) systems focused on heat transfer and enhancement techniques employed in PCMs to effectively charge and discharge latent heat energy, and the formulation of the phase change problem. The main categories of PCMs are classified and briefly described, and heat transfer enhancement technologies, namely dispersion of low‐density materials, use of porous materials, metal matrices and encapsulation, incorporation of extended surfaces and fins, utilisation of heat pipes, cascaded storage, and direct heat transfer techniques, are also discussed in detail. Additionally, a two‐dimensional heat transfer simulation model of an LHS system is developed using the control volume technique to solve the phase change problem. Furthermore, a three‐dimensional numerical simulation model of an LHS is built to investigate the quasi‐steady state and transient heat transfer in PCMs. Finally, several future research directions are provided. Development of latent heat storage (LHS) systems focused on heat transfer and enhancement techniques used in phase change materials (PCMs) is reviewed The main categories of PCMs are classified, and its characteristic properties are briefly described Heat transfer enhancement technologies are also discussed in detail A numerical simulation model of two‐dimensional heat transfer and another with three dimensions for the LHS are included Several future research directions are provided